Prognoz vysshikh dostizhenii sil'neishikh tyazheloatletok na XXVII Olimpiiskikh Igrakh b Sidnee - Medvedev, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
From the international situation and the prerformance development and performance dynamics over the last years a forecast of highest achievements of elite female weight lifters in XXVII Olympic Games in Sydney is made.